PSEUDOANEURISMA AKIBAT FISTULA KAROTISKAVERNOSUS PASCA TRAUMA SEBUAH LAPORAN KASUS - M.Z Arifin*, Sevline Estethia Ompusunggu*. (NEURONA, 2010)
INTRODUCTION CAROTIDCAVERNOUS FISTULAS CCFS ARE ABNORMAL COMMUNICATIONS BETWEEN CAROTID ARTERIAL SYSTEM AND CAVERNOUS SINUS THE MOST FREQUENT CAUSE OF CCFS IS TRAUMA YOUNG MEN MORE LIKELY TO DEVELOP TRAUMATIC CCFS MOST OFTEN CCFS EVOLVE AND APPARENT OVER DAYS OR WEEKS DIAGNOSIS CAN BE ESTABLISHED FROM CLINICAL EXAMINATION MRI CT SCAN AND ANGIOGRAPHY